2008
DOI: 10.1002/app.28639
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of glycidyl azide polymer‐based urethane network formation

Abstract: Reactions between hydroxyl-terminated glycidyl azide polymer (GAP) and different isocyanate curatives such as toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), and methylene diicyclohexyl isocyanate (MDCI) at various temperatures viz. 30, 40, 50, and 608C were followed by Fourier transform infra red spectroscopy. The reactions were found to follow second-order kinetics. With TDI and IPDI at 308C, a two-stage reaction was observed. For GAP-TDI system, the second stage was slower than the first while f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…The comparative mean values of the Shore hardness are listed in Table 2. It is well known that the degree of cross linking or polymerization in a polymer may be affected by the amount of curing agent used to cure the polymer [9][10][11]. These results indicated that the hardness of the samples increased with the increase in percent of acrylate.…”
Section: Shore Hardness Of Gap Cured With Acrylatesupporting
confidence: 71%
See 1 more Smart Citation
“…The comparative mean values of the Shore hardness are listed in Table 2. It is well known that the degree of cross linking or polymerization in a polymer may be affected by the amount of curing agent used to cure the polymer [9][10][11]. These results indicated that the hardness of the samples increased with the increase in percent of acrylate.…”
Section: Shore Hardness Of Gap Cured With Acrylatesupporting
confidence: 71%
“…Azido polymers can undergo dipolar cycloaddition reactions with acrylates resulting in a cross-linked network of polymer containing triazole rings. GAP cured with polyfunctional acrylate has been reported as a binder for gas generating compositions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…New energetic polymers such as glycidyl azide polymer (GAP), polyglycidyl nitrate (PGN), polynitromethyloxetane (PLN) and 3,3-bis(azydomethyl)oxetane (BAMO) have become one of the promising materials that could satisfy these requirements [3,4]. Among them, glycidyl azide polymer (GAP) is one of the most thoroughly studied energetic binder which its synthesis, performance, and applications have been reported in detail by several researchers [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the curing temperature, an important factor to curing kinetics process, must be matched with the type of curing agents. When the GAP were cured with different diisocyanates at 30°C, both GAP/TDI and GAP/IPDI systems obviously showed a two‐stage reaction due to the difference in the reactivity of two isocyanate groups in the same curing agent, resulting in the instability of curing kinetics process. Although increasing curing temperature can make such two‐stage reaction narrow down and even vanish, too fast and severe curing kinetics process under higher temperature usually leads to the decrease in the quality of composite solid propellant.…”
Section: Introductionmentioning
confidence: 99%